2010
DOI: 10.1080/14789949.2010.511241
|View full text |Cite
|
Sign up to set email alerts
|

A site visit survey of 101 mental health liaison and diversion schemes in England

Abstract: This article presents the findings of a unique site visit audit of all known assessment, liaison and diversion schemes in England. The Lord Bradley Review placed great importance upon such teams to be a hub of service provision for individuals with mental health needs who pass through the criminal justice system. This study, undertaken to inform the Lord Bradley Review (2009, www.dh.gov.uk/en/Publicationsandstatistics/Publications/ PublicationsPolicyAndGuidance/DH_098694), demonstrates that although these sche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…However, such services have developed in localised, ad hoc ways, leading to inadequate staffing; operating hours which frequently exclude evenings and weekends and confusion over which client group should be targeted (Pakes & Winstone, 2010;Senior, Lennox, Noga, & Shaw, 2011). Due to the limitations of current screening processes, CJMHL&D services see only a minority of those in custody and may be missing a large proportion of people who could benefit from their service (Senior, et al, 2011).…”
Section: Introductionmentioning
confidence: 98%
“…However, such services have developed in localised, ad hoc ways, leading to inadequate staffing; operating hours which frequently exclude evenings and weekends and confusion over which client group should be targeted (Pakes & Winstone, 2010;Senior, Lennox, Noga, & Shaw, 2011). Due to the limitations of current screening processes, CJMHL&D services see only a minority of those in custody and may be missing a large proportion of people who could benefit from their service (Senior, et al, 2011).…”
Section: Introductionmentioning
confidence: 98%
“…Some writers have limited the definition of diversion to the provision of inpatient admissions, reserving the term “liaison” for non-inpatient community treatment arrangements [2,3]. While there are many descriptions of effective police-station and court-based diversion services for local areas, reviews of diversion services have highlighted inequalities between local areas, and the need for standardisation of approach to enable equal access over larger geographical areas and population aggregates [2-6]. …”
Section: Introductionmentioning
confidence: 99%
“…Policy and expert guidelines exist to advise on the organization of mental health services in prisons [4-6]. The UN Declaration of Rights of the Mentally Ill [7] emphasises that persons with major mental illness should have equal rights with their non-mentally ill counterparts, including equal rights to bail and liberty.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This includes improving recognition and screening, mental health assessment, and signposting to health and social care services when appropriate, and the new national programme has supported the roll out of 20 pathfinder sites to implement the liaison and diversion schemes across England and Wales (Clapper, 2012). However, research into the effectiveness of these teams has indicated patchiness in provision, with many areas still having no provision (Pakes and Winstone, 2010).…”
mentioning
confidence: 99%